Elementary Signal Detection Theory. - Wickens, Thomas D. (Oxford University Press, 2001)
How do humans discriminate? And is it measurable? In this book Thomas Wickens explains signal detection theory, which in essence, was devised to provide an explanation for the human ability to discriminate and how might we implement reliable measures to quantify this ability.